Hospital-acquired gastroenteritis at a referral hospital in Gaborone, Botswana - Welch, Henry; Goldfarb, David M.; Moorad, Banno; Mokomane, Margaret; Smieja, Marek; Chakalisa, Unoda; Steenhoff, Andrew P; Finalle, Rodney; Coffin, Susan E (International Journal of Infection Control, 2017)
Background: Hospital-acquired infections, including hospital-acquired gastroenteritis (HAGE), are well documented in Western countries but little is known about these infections in sub-Saharan Africa. Aim: To determine the incidence of and explore modifiable risk factors for HAGE. Methods: A prospective cohort study of children <13 years with HAGE admitted to Princess Marina Hospital in Gaborone, Botswana was performed. HAGE was defined as new-onset GE >72 hours after admission or upon admission after recent discharge for a non-GE illness. Children were followed until discharge to ascertain therapies used and adverse outcomes. Enteric pathogens were identified by multiplex PCR. Findings: Virtually all of the 32 children with HAGE were < 2 years (n=30, 94%) and most were male (n=19, 59%). Few had HIV infection (n=6, 19%), severe malnutrition (n=8, 25%), or a history of vitamin A use in the past 6 months (n=2, 6%). The mean monthly incidence of HAGE was 2.3 per 1000 patient days, and associated with the monthly number of community-acquired gastroenteritis (CAGE) admissions (IRR 1.02, 95% CI 1.00, 1.04, p=0.025). A stool pathogen was detected in 15/27 (56%) children, including norovirus (n=7, 26%) and rotavirus (n=5, 18%). Most children received oral rehydration solution (n=26, 81%), or IV fluids (n=9, 28%). Antibiotics were administered to 5 (16%) children. Two (6%) children with HAGE were admitted to the ICU and 4 (12%) died. Conclusions: We found HAGE was relatively common and associated with severe outcomes. The monthly incidence of HAGE was associated with CAGE admissions. Common pathogens included norovirus and rotavirus.